Letter - Taunton Trades and Labour Council, 7 May 1926 (Taunton)
1926-05-07 "Letter - Taunton Trades and Labour Council, 7 May 1926" [g0344001.jpg], 7 May 1926, Taunton Trades and Labour Council Local Organisation